Non-EFL Students Vocabulary Learning Strategies - Holifah Holifah; Kurniasih Kurniasih (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
As development progresses, international competition and cooperation cannot be avoided. This phenomenon will encourage students to participate in it. Therefore, the ability to speak English is an important component to be involved in this phenomenon. Various countries in the world have been competing to apply English to their children from an early age. This study will focus on students' perceptions of vocabulary strategies in learning English. This study involved 32 participants from different universities and data collection was done through a questionnaire. The results showed that the participants liked to use learning strategies, and they agreed that using strategies in learning could improve the quality of vocabulary learning. As well as train their language skills, reasoning abilities, and understanding of the content of word use. Even though they are not consistent with just one strategy, from the data, presented, they almost ever do all the strategies offered.